Characterization of arcs by products and diagonals - Katsuura, Hidefumi (Topology Proceedings, 2022)
We prove that a continuum $X$ is a Hausdorff arc if, and only if, $X^2-D$ is not connected, where $D$ is the diagonal of $X^2$.